2014
DOI: 10.1002/cssc.201301218
|View full text |Cite
|
Sign up to set email alerts
|

Selective Glycerol Oxidation by Electrocatalytic Dehydrogenation

Abstract: This study demonstrates that an electrochemical dehydrogenation process can be used to oxidize glycerol to glyceraldehyde and glyceric acid even without using stoichiometric chemical oxidants. A glyceric acid selectivity of 87.0 % at 91.8 % glycerol conversion was obtained in an electrocatalytic batch reactor. A continuous-flow electrocatalytic reactor had over an 80 % high glyceric acid selectivity at 10 % glycerol conversion, as well as greater reaction rates than either an electrocatalytic or a conventional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
52
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 42 publications
(31 reference statements)
2
52
0
Order By: Relevance
“…Besides, the subsequent tedious extraction process also limited its large‐scale application. Alternatively, GLY conversion by electrochemical oxidation has recently attracted much attention . Electro‐oxidation of GLY is a totally green process, which does not involve any toxic oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, the subsequent tedious extraction process also limited its large‐scale application. Alternatively, GLY conversion by electrochemical oxidation has recently attracted much attention . Electro‐oxidation of GLY is a totally green process, which does not involve any toxic oxidants.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, efforts have been devoted to developing efficient electrochemical conversion technologies to produce value‐added chemicals and/or energy from biomass‐derived oxygenates such as glycerol . The electrocatalytic conversion process of glycerol is a promising technology that can produce valuable chemicals such as dihydroxyacetone, glyceraldehyde, and glyceric acid by selective oxidation reaction and electrical energy by a full oxidization reaction . In particular, full glycerol oxidation has been considered a promising reaction for direct alcohol fuel cells (DAFC), because glycerol is nonflammable and has environmentally friendly properties; it also possesses high theoretical energy density, with relatively low price and simple purification steps .…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Kim et al obtained selectivities values of 87% and 50% for GLA and GALD, respectively, from carbon supported Pt catalyst. 19 Zhang et al synthesized a PtCo/RGO catalyst with a GLA selectivity of 85.9%, which was higher than those of Pt/RGO and Co/RGO. 20 Dai et al studied GLY oxidation over an AuPt catalyst which showed a selectivity of 70% for lactic acid.…”
Section: Introductionmentioning
confidence: 97%